What are you looking at? - Lin, Wahlene Fangjun. (2011)
This project’s theme focuses on the link between females and the effects of consumerism. I hope to raise awareness about the effects of the idealisation of female aesthetics on women consumerism through this project. Images were made through digital means by using a digital single-lens reflex camera (SLR) and a computer. The series also include employing the self as a subject to show the consumption of products. Next, a book featuring the pages of various overlaid advertisements was made and twenty one images were successfully selected. Though the images resembled a painting, not much eye movement could be achieved for each image as there was little play with depth of field. Technical details might also be judged against with the choice of using digital manipulation. In conclusion, the Final Year Project has come to an end as a school project but it will prolonged in due time as a personal project.